Pristimerin exhibits anti-cancer activity by inducing ER stress and AKT/GSK3β pathway through increasing intracellular ROS production in human esophageal cancer cells - Hu, Wei-Bin; Liu, Yi-Ting; Li, Jing; Wang, Ying; Sun, Xuan-Zi; Hua, Ming-Yu; Liu, Xue-Ting; Hui, Bei-Na (Toxicology in vitro, 2024)
Pristimerin (Pris), a bioactive triterpenoid compound extracted from the Celastraceae and Hippocrateaceae families, has been reported to exhibit an anti-cancer property on various cancers. However, the effects of Pris on esophageal cancer are poorly investigated. This current study sought to explore the activity and underlying mechanism of Pris against human esophageal squamous cell carcinoma (ESCC) cells. We demonstrated that Pris showed cytotoxicity in TE-1 and TE-10 ESCC cell lines, and significantly inhibited cell viability in a concentration dependent manner. Pris induced G0/G1 phase arrest and triggered apoptosis. It was also observed that the intracellular ROS level was remarkedly increased by Pris treatment. Besides, the function of Pris mediating the activation of ER stress and the inhibition of AKT/GSK3β signaling pathway in TE-1 and TE-10 cells was further confirmed, which resulted in cell growth inhibition. And moreover, we revealed that all of the above pathways were regulated through ROS generation. In conclusion, our findings suggested that Pris might be considered as a novel natural compound for the developing anti-cancer drug candidate for human esophageal cancer. •Pristimerin exhibited notable anti-esophageal cancer activity.•Pristimerin induced cell cycle arrest, promoted apoptosis, and increased ROS level.•Pristimerin regulated AKT/GSK3β pathway via ROS production to inhibit cell growth.•Pristimerin suppressed cell growth through ROS-mediated ER stress.